2017
DOI: 10.3390/en10030307
|View full text |Cite
|
Sign up to set email alerts
|

Wind Energy Potential and Power Law Indexes Assessment for Selected Near-Coastal Sites in Malaysia

Abstract: This paper investigated the wind energy potential by analysing a certain amount of gathered 10-min measured data at four stations located at coastal sites in Malaysia, i.e., Kudat, Mersing, Kijal, and Langkawi. The wind data are collected from a total of four new wind measurement masts with sensors mounted at various heights on the tower. The measured data have enabled the establishment of wind resource maps and the power law indexes (PLIs) analysis. In addition, the dependence of PLI upon surface temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 45 publications
1
45
0
Order By: Relevance
“…Different methods can be used for wind extrapolation; the power law is used in this study for its simplicity. This law is considered a useful tool and is commonly used in the assessment of wind power potential to extrapolate wind speed data at different heights, which is defined as [52,53]…”
Section: Wind Speed Extrapolationmentioning
confidence: 99%
“…Different methods can be used for wind extrapolation; the power law is used in this study for its simplicity. This law is considered a useful tool and is commonly used in the assessment of wind power potential to extrapolate wind speed data at different heights, which is defined as [52,53]…”
Section: Wind Speed Extrapolationmentioning
confidence: 99%
“…Becerra et al (2017) presented a techno-financial evaluation of two Chilean locations with promising wind energy potential: Laguna Verde placed in the central region of the country and Porvenir in the southern region. Albani and Ibrahim (2017) investigated the wind energy potential by analysing a certain amount of gathered 10 minute measured data at four stations located at the coastal sites in Malaysia, namely, Kudat, Mersing, Kijal and Langkawi. They found that only Kudat and Mersing had a promising potential to develop a medium capacity of wind turbine power, while the other sites were suitable only for wind turbines at a smaller scale.…”
Section: Introductionmentioning
confidence: 99%
“…From the West, Kudat faces the South China Sea and it faces the Sulu Sea at the east direction. As reported by numerous scholars, Kudat is a well-known region that has promising wind energy potential in Malaysia [46][47][48][49]. The wind speed data were collected from the measurement mast developed by Universiti Malaysia Terengganu.…”
Section: Case Study Site and Energy Analysismentioning
confidence: 99%